To drink or not to drink, that is the question: A discussion paper about traditional verses newer fasting guidelines - Jessica Muscat; Paula Foran (Journal of Perioperative Nursing, 2025)
Introduction: Australia has seen a rapid increase in the number of hospitals reviewing their pre-operative fasting times. However, many hospitals still adhere to traditional fasting protocols, and in many cases, even when updated guidelines are implemented, fasting times are often extended in clinical practice resulting in poorer patient outcomes. This highlights the need for greater understanding of how longer fasting contributes to adverse symptoms and outcomes including thirst, dehydration, dry mouth, post-operative nausea and vomiting, haemodynamic instability and prolonged hospital stays. Discussion: This discussion paper aims to shine a light on the adverse outcomes associated with traditional fasting protocols, compared to the benefits of more liberal fasting practices such as those provided by The Australian and New Zealand College of Anaesthetists (ANZCA) fasting guidelines. It also aims to provide greater understanding for all nurses providing pre-operative care of how to ensure the safe implementation and ongoing adherence to these changes in fasting practice. Conclusion: Due to the many variables in patients’ conditions and pharmacological treatments, it is no longer appropriate to have a ‘one size fits all’ traditional approach to pre-operative fasting. Despite robust evidence supporting the safety of clear fluids two hours before surgery, patients being prepared for surgery are often still denied fluids for longer periods of time by nurses. Nurses from any specialty, including day of surgery admissions, accident and emergency, intensive care and medical or surgical wards, who care for patients pre-operatively, all need to understand the concepts and theoretical background behind traditional and more liberal fasting protocols so they can provide informed, safe care and more comfortable perioperative outcomes by following the ANZCA fasting guidelines.